1970
DOI: 10.3126/kuset.v4i1.2883
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Antimicrobial Evaluations of some Medicinal Plants of Nepal

Abstract: Use of plant based drugs and chemicals for curing various ailments and personal adornment is as old as human civilization. Plants and plant-based medicaments are the basis of many of the modern pharmaceuticals we use today for our various ailments. The aim of the study was to find out the bioactive chemical constituents and to evaluate the antimicrobial activity of the ethanolic extract of traditionally used eight medicinal plants of Nepal. A qualitative phytochemical analysis was performed for the detection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 6 publications
6
46
1
Order By: Relevance
“…These results are almost similar to those shown by other works on the antimicrobial activity of essential oil of E. globulus leaves as well as those of similar species [14,[21][22][23][24][25][26][27][28][29] , and confirms its traditional uses [26,30,31] .…”
Section: Discussionsupporting
confidence: 80%
“…These results are almost similar to those shown by other works on the antimicrobial activity of essential oil of E. globulus leaves as well as those of similar species [14,[21][22][23][24][25][26][27][28][29] , and confirms its traditional uses [26,30,31] .…”
Section: Discussionsupporting
confidence: 80%
“…However, tannins, terpenoids and resins are absent. Steroids, glycosides, terpenoids and flavonoids were found in C. longa while tannins were absent (Chhetri et al, 2008). Anukwuorji et al (2013) revealed that in Z. officinale saponins were abundantly present while tannins, glycosides and flavonoids were moderately present and steroids were not detected.…”
Section: Discussionmentioning
confidence: 99%
“…The extracts of K. senegalensis stem bark was subjected to preliminary phytochemical analysis to test for the presence/absence of the various classes of active chemical constituent such as saponins, flavonoids, tannins, alkaloids, oxalate, phytate and cyanogenic glycoside using standard laboratory techniques as reported by Sood et al (2012) and Chhetri et al (2008). Quantitative phytochemical analysis of K. senegalensis was also determined using standard biochemical techniques.…”
Section: Preliminary Phytochemical Determinationmentioning
confidence: 99%